THE DEVELOPMENT OF PORONG ESTUARY - Undang Hernawan (Bulletin of the Marine Geology, 2017)
Coastal zone is an area of interaction between the land and the sea. Coastal dynamic is influenced by many factors, such as sedimentation and current. Development of an area in the coastal zone such as estuary is also influenced by suck factors. Development of porong estuary is analyzed by interpretation of Image data, i.e. Landsat TM data that acquired in July, 29th 1975, August, 17th 1994, August, 17th 2000, May, 19th 2002 and Quickbird imagery that acquired in April, 25th 2008. Field survey has been done on April 2008. Based on data interpretation, there are accretion and abrasion in this area. The accretion in the southern part of Porong estuary between 1975 – 2008 is about 33.15 km or about 3.15 km/year equivalent to 1,492.29 Ha. The abrasion area in the northern part of Porong estuary in 33 years since 1975 till 2008 is around 0.5 km or aproximately 15.15 m/year equivalent to 222.45 Ha of wide or 6.802 Ha/year. Development of Porong delta, especially in the southern part of Porong estuary, is caused by change of pattern and main stream of Porong River from the noth to the south. This river delivered large volume of sediments and precipated at this area without or minor influence from the sea. Porong delta is a fluvial delta. Coastal characteristic is mangrove, muddy sediment and locally is sand sediment. Land use in this area is fish pond and mangrove.